Introducing the Practice Dive Approach: an extension of co-creation in physical activity promotion and health promotion - Popp, Johanna; Carl, Johannes; Grüne, Eva; Pfeifer, Klaus (Health promotion international, 2021)
Recently, there has been increasing interest in co-creation utilized for physical activity (PA) promotion and health promotion. Co-creation involves researchers and non-academic stakeholders conjointly developing and implementing interventions. In addition to the frequently reported benefits of co-creation, critical voices highlight the associated challenges (e.g. different interests that inhibit interaction). So far, research has not identified concrete solutions to these challenges and the limitations of co-creation. This article aims to introduce the Practice Dive Approach as a potential way to strengthen cooperation between researchers and non-academic stakeholders. We build on real-life experiences from a German research project, in which researchers moved into practice to familiarize themselves with the settings and end-users. After conducting a literature search on related concepts in PA/health promotion, we developed a comprehensive approach to fostering multi-sectoral cooperation. The introduced Practice Dive Approach assumes that a significant contribution to better cooperation among co-creators is the temporal immersion of researchers in their setting of interest, which has the potential to improve the success of co-creation in the PA/health promotion field. A four-level typology characterizes the intensity of researcher interactions with the setting and the non-academic stakeholders. Potential beneficial effects for both researchers and non-academic stakeholders can be hypothesized (e.g. familiarity with the setting structures and increased understanding of the end-users), while simultaneously, some challenges need to be considered. Future research should aim to validate the concept and its postulated effects.
Created from Fastlane, Scopus look-up
Keywords: Cooperative Planning; co-production; participation; transdisciplinarity